Energy efficiency development in the German and Colombian energy intensive sectors: A non-parametric analysis (2009)
This paper measures energy efficiency development in non-energy-intensive sectors (NEISs) in Germany and Colombia from a production-based theoretical framework using Data Envelopment Analysis (DEA). Using data from the German and Colombian Annual Surveys of Industries from 1998 to 2005, the analysis compares energy efficiency performances in German and Colombian NEISs at two levels of aggregation and then applies several alternative models. The results show considerable variation in energy efficiency performance in the NEISs of both countries. Comparing the results across models, it was found that in the German and Colombian NEISs, the measures of energy efficiency are similar, indicating that an appropriate combination of technical efficiency and cost minimisation are necessary to improve energy efficiency.